Analisis Penentuan Pola Produksi Dalam Upaya Meminimalisasi Biaya Produksi Dengan Metode Incremental Cost - Aneke Ayu Putri Ningtyas; Setyo Adjie; Wijianto Wijianto (ASSET: Jurnal Manajemen dan Bisnis, 2018)
This study discusses efforts to minimize production costs at the Ponorogo "Sweep Jagad" Production House by taking into account additional costs that may occur during production activities, including saving costs, overtime costs, subcontracting costs, and labor turnover costs.  Through the application of production patterns with three alternatives, namely constant production patterns, corrugated production patterns, and moderate production patterns, a clear picture of production can be carried out by companies in the future.  The results obtained indicate that there are significant differences in the production costs of the three production patterns.  Value of costs in a constant production pattern of Rp.  5,240,500, then the corrugated production pattern of Rp. 1,676,000, then the moderate production pattern of Rp.  6,744,500.  Therefore the production pattern that is able to minimize production costs is a corrugated production pattern.